IMPLEMENTASI SISTEM PEMBELAJARAN EFEKTIF SEBAGAI STRATEGI PENGUATAN PROFESIONALISME GURU DALAM ERA DIGITAL - Joko, Joko; Rachmadio, R.Edy; Nugraha, Derry (MAJU : Indonesian Journal of Community Empowerment, 2024)
This research aims to analyze teacher professionalism strengthening through the implementation of effective learning systems. Using a mixed-method approach, the study was conducted on 100 teachers selected through purposive sampling. Data collection included questionnaires, in-depth interviews with 20 teachers, learning observations, and focus group discussions. The results showed significant improvements in teacher competencies: pedagogical (25%), professional (28%), learning technology utilization (35%), and evaluation skills (30%). The implementation of effective learning systems positively impacted student learning motivation (75%) and learning outcomes (68%). Key supporting factors included policy support and availability of continuous professional development programs, while inhibiting factors included administrative burden and limited technology access. The teacher professionalism strengthening program proved effective in improving learning quality, although it still requires strengthening of the mentoring system and development of digital learning platforms..